A novel and simple classification for ligamentum teres pathology based on joint hypermobility. Issue 2 (16th October 2017) - O'Donnell, John M; Arora, Manit
Abstract: Ligamentum teres (LT) pathology (including synovitis, partial and complete tears) is common at the time of hip arthroscopy with a reported prevalence of 51–90%. Currently, there are four published classifications of LT injuries and tears. The majority focuses on differentiating partial from full thickness tears, whereas a more recently published classification also incorporates the presumed underlying mechanism of pathology. A recent review of the current classification systems found that all are deficient for lack of inclusion of what constitutes a normal ligament, lack of inclusion of synovitis as a source of pathology and lack of inclusion of hypermobility as part of the treatment algorithm. Also, the two most commonly used classification systems have only fair inter-observer reliability. Recent work has found that underlying joint hypermobility plays an important role in LT pathology and that the addition of capsular plication/suture at the time of surgery for LT pathology improves outcomes and reduces re-tear rates. In order to address these problems which have been identified with the currently available classification systems, we propose a novel and simple classification for LT pathology based on underlying joint hypermobility [as assessed by the Beighton test score (BTS)]. LT pathology is used to divide all patients into four types: 0 normal (which includes minor fraying), 1 synovitis (which would also include minor fraying), 2 partial tear and 3 complete tear. Further, all types are subdivided into two groups: Group A patients have no clinical evidence of joint hypermobility (BTS < 3), whereas Group B patients do have clinical evidence of joint hypermobility (BTS ≥ 4). On the basis of this classification system and the available literature, we have also developed a treatment algorithm for LT pathology.